The Gestapo and German society: enforcing racial policy 1933-1945 - Gellately, Robert (Clarendon [u.a.], 1990)
Robert Gellately: The Gestapo and German Society. Enforcing Racial Policy 1933-1945. Clarendon Press, Oxford 1990. 297 Seiten, 35 britische Pfund